AUDIOVISUAL TRANSLATION OF POLITENESS IN "THE LAST SAMURAI" FILM: A STUDY OF ENGLISH INTO INDONESIAN SUBTITLE - Permana, Yusup Aji (2014)
The study is entitled "Audiovisual Translation of Politeness in 'The Last Samurai' Film: A Study of English into Indonesian Subtitle". It aims to analyze subtitle strategies used in subtitling texts that contain politeness strategies found in the film. The study applied a qualitative descriptive method in collecting and descripting the data. The concept of Brown and Levinson's (1987) politeness strategies and Gottlieb's (1992) subtitling theory were referred to. There were 465 politeness strategies occurrences in the selected data. Four types of politeness strategies were found: positive politeness 176 items (37.93%), negative politeness 139 items (29.95%), bald on-record 120 items (25.87%), and off-record 30 items (6.25%). Nine of ten subtitle strategies were applied in subtitling texts which contain politeness strategies, namely: expansion, paraphrase, transfer, imitation, transcription, dislocation, condensation, decimation and deletion. The most frequently used strategy was transfer with 218 items (46.89%) and the least used strategy was transcription with 1 item (0.21%). The dominant phenomenon reveals the translator's tendency in applying transfer as a strategy to render all types of politeness strategyies in the source language texts into the target language texts at equal degree. Keywords: audiovisual translation, subtitle strategies, politeness strategies. Penilitian ini berjudul "Audiovisual Translation of Politeness in "The Last Samurai" Film: A Study of English into Indonesian Subtitle". Penelitian ini bertujuan untuk menganalisa penggunaan strategi dalam menerjemahkan teks yang mengandung strategi kesopanan yang ditemukan di dalam film. Metode kualitatif deskriptif digunakan dalam mengumpulkan dan mendeskripsikan data penelitian ini. Konsep strategi kesopanan Brown dan Levinson (1987) dan teori penerjemahan subtitle Gottlieb (1994) digunakan sebagai landasan teori. Dalam temuan penelitian ini, terdapat 465 kemunculan strategi kesopanan dalam data yang terkumpul. Empat tipe strategi kesopanan ditemukan, diantaranya: positive politeness, 176 kemunculan (37.93%), negative politeness, 139 kemunculan (29.95%), bald on-record, 120 kemunculan (25.87%), dan off-record, 30 kemunculan (6.25%). Sembilan dari sepuluh strategi penerjemahan digunakan dalam menerjemahkan teks yang mengandung strategi kesopanan, diantaranya: expansion, paraphrase, transfer, imitation, transcription, dislocation, condensation, decimation, dan deletion. Strategi yang paling sering digunakan adalah transfer dengan 218 item (46.89%) dan strategi yang paling jarang digunakan adalah transcription dengan 1 item (0.21%). Fenomena yang dominan menunjukan kecenderungan penerjemah dalam menggunakan transfer sebagai strategi untuk menerjemahkan semua tipe fitur strategi kesopanan dari teks sumber ke teks target pada derajat yang sama. Kata kunci: audiovisual translation, strategi penerjemahan subtitle, strategi kesopanan.